Calcium lignosulfonate-induced modification of soil chemical properties improves physiological traits and grain quality of maize (Zea mays) under salinity stress - Alhaj Hamoud, Yousef; Shaghaleh, Hiba; Zhang, Ke; Okla, Mohammad K.; Alaraidh, Ibrahim A.; AbdElgawad, Hamada; Sheteiwy, Mohamed S. (Frontiers in Plant Science, 2024)
Salinity negatively affects maize productivity. However, calcium lignosulfonate (CLS) could improve soil properties and maize productivity. Therefore, we evaluated the effects of CLS application on soil chemical properties, plant physiology and grain quality of maize under salinity stress. Thus, this experiment was conducted using three CLS application rates, CLS0, CLS5, and CLS10, corresponding to 0%, 5%, and 10% of soil mass, for three irrigation water salinity (WS) levels WS0.5, WS2.5, and WS5.5 corresponding to 0.5 and 2.5 and 5.5 dS/m, respectively. Resultsshow that the WS0.5 × CLS10 combination increased potassium (K 0.167 g/kg), and calcium (Ca, 0.39 g/kg) values while reducing the sodium (Na, 0.23 g/kg) content in soil. However, the treatment WS5.5 × CLS0 decreased K (0.120 g/kg), and Ca (0.15 g/kg) values while increasing Na (0.75 g/kg) content in soil. The root activity was larger in WS0.5 × CLS10 than in WS5.5 × CLS0, as the former combination enlarged K and Ca contents in the root while the latter decreased their values. The leaf glutamine synthetase (953.9 µmol/(g.h)) and nitrate reductase (40.39 µg/(g.h))were higher in WS0.5 × CLS10 than in WS5.5 × CLS0 at 573.4 µmol/(g.h) and 20.76 µg/(g.h), leading to the improvement in cell progression cycle, as revealed by lower malonaldehyde level (6.57 µmol/g). The K and Ca contents in the leaf (881, 278 mg/plant), stem (1314, 731 mg/plant), and grains (1330, 1117 mg/plant) were greater in WS0.5 × CLS10 than in WS5.5 × CLS0 at (146, 21 mg/plant), (201, 159 mg/plant) and (206, 157 mg/plant), respectively. Therefore, the maize was more resistance to salt stress under the CLS10 level, as a 7.34% decline in yield was noticed when salinity surpassed the threshold value (5.96 dS/m). The protein (13.6 %) and starch (89.2 %) contents were greater in WS0.5 × CLS10 than in WS5.5 × CLS0 (6.1 %) and (67.0 %), respectively. This study reveals that CLS addition can alleviate the adverse impacts of salinity on soil quality and maize productivity. Thus, CLS application could be used as an effective soil amendment when irrigating with saline water for sustainable maize production.